Experimental cryo-irrigation of the knee joint. - Chen, S C (1986)
Experiments have been carried out to test the feasibility of using cryo-irrigation as a means of ablating the synovium in the rheumatoid knee joint. Cryo-irrigation was performed by a cooling machine and pump, which circulated cold 200/10 centistoke (cSt) silicone through the knee joint of rabbits anaesthetised with intravenous (IV) 'Saffan'. Fluid left the joint at -5 to -10 degrees C. Sixteen normal New Zealand rabbits received cryo-irrigation of one knee joint for 10-20 minutes and were killed at one day, and one, two, and 12 weeks thereafter. Judged by radioactive sulphate incorporation there was no impairment of chondrocyte function in the articular cartilage of irrigated joints. Histological examination showed mild synovitis and some loss of staining of superficial cartilage in 6/16 irrigated joints (v 1/16 control joints). Similar treatment of rabbit joints in which the Glynn model of synovitis had been induced showed marked reduction of synovitis 14-45 days after silicone treatment. Nine of 26 animals in which synovitis was induced in both knees and cryo-irrigation performed in one knee died either immediately postoperatively or during the next week. These deaths remain unexplained. A single dog received cryo-irrigation of one knee (-6 to -9 degrees C for 22 min) and remained perfectly well up to sacrifice at six months, when the joint appeared histologically completely normal.